2017
DOI: 10.1007/s10522-017-9684-x
|View full text |Cite
|
Sign up to set email alerts
|

Aging, frailty and complex networks

Abstract: When people age their mortality rate increases exponentially, following Gompertz's law. Even so, individuals do not die from old age. Instead, they accumulate age-related illnesses and conditions and so become increasingly vulnerable to death from various external and internal stressors. As a measure of such vulnerability, frailty can be quantified using the frailty index (FI). Larger values of the FI are strongly associated with mortality and other adverse health outcomes. This association, and the insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 78 publications
3
83
0
Order By: Relevance
“…We have used a complex network to model human aging and relate it to frailty ( Figure 1) (Taneja et al, 2016;Farrell et al, 2016;Mitnitski et al, 2017b). Nodes of the network can each be either undamaged or damaged (thereby representing deficits); damaged nodes can also be repaired, reflecting an important source of the observed dynamics of frailty (Mitnitski et al, 2017a), also account for a possibility to recover after being damaged.…”
Section: Resultsmentioning
confidence: 99%
“…We have used a complex network to model human aging and relate it to frailty ( Figure 1) (Taneja et al, 2016;Farrell et al, 2016;Mitnitski et al, 2017b). Nodes of the network can each be either undamaged or damaged (thereby representing deficits); damaged nodes can also be repaired, reflecting an important source of the observed dynamics of frailty (Mitnitski et al, 2017a), also account for a possibility to recover after being damaged.…”
Section: Resultsmentioning
confidence: 99%
“…Exponential growth of health deficits can be motivated with a microfoundation of aging from reliability theory (Gavrilov and Gavrilova, 1991;Dalgaard et al, 2017) and from network theory (Mitnitski et al, 2017). Individuals born in the other seasons also accumulate health deficits exponentially but the speed of aging may differ.…”
Section: Data/methodsmentioning
confidence: 99%
“…Specifically it has been shown that organisms constructed in parallel from non-aging elements age according to the Gompertz-law of mortality when the number of initially nonfunctioning elements follows a Poisson distribution (Gavrilov and Gavrilova, 1991). A recent study uses network theory to explain human aging and provides a microfounded explanation for why an unweighted health deficit index provides an accurate measure of aging and mortality (Mitnitski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organisms do not ultimately die because they run out of cells, but because cellular damage manifests as larger scale problems in tissues and organs, through a cascade of interactions. It remains unclear how failures dynamically propagate and accumulate to lead to frailty, aging related diseases, and ultimately, death [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%